PATHOLOGICAL PHYSIOLOGY OF PERIPHERAL CIRCULATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The work examines the general blood circulation and studies typical peripheral disorders. It is shown that pathological arterial hyperemia can be divided by the mechanism of development into neurogenic and developing under the direct action of metabolites on the walls of blood vessels. Characteristic signs of ischemia and classification of thrombi are given.